HUBUNGAN KEMAMPUAN BERPIKIR KRITIS DAN KEMAMPUAN BERPIKIR KREATIF PADA PELAJARAN IPAS SISWA SD - Br Kembaren, Desy Putri Egina; Ani Rusilowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking skills and creative thinking skills are essential competencies in the21st century. There is a growing perspective that these two thinking skills can bedeveloped simultaneously. Therefore, this study aims to determine the relationshipbetween critical thinking skills and creative thinking skills in the IPAS (Science,Environment, Technology, and Society) subject among elementary school students.This research uses a quantitative method with a correlational approach and employstests as the data collection technique. The test instruments are divided into twotypes: a two-tier multiple-choice test to measure critical thinking skills, which wasdeveloped based on four indicators—focus, reason, inference, and situation; and anessay test to measure creative thinking skills, with indicators including fluency,elaboration, flexibility, and originality. The population of this study consists of allsixth-grade students at SD Negeri 1 Jambu Ilir, with one class totaling 34 students.The correlation test results indicate a relationship between critical thinking skills andcreative thinking skills. The regression coefficient result shows a value of 0.551,indicating that critical thinking skills influence 55% of creative thinking skills.